EDUKASI PERLINDUNGAN ANAK DENGAN MODEL PEMBELAJARAN ASSURANCE-RELEVANCE-INTEREST-ASSESSMENT-SATISFACTION: ERA NEW NORMAL - Hamidah Hamidah (IKIP SILIWANGI, 2020)
Lack of teacher knowledge on the importance of caring for child psychology in packing the online learning process. The purpose of the activity is educating participants, especially teachers, that in the application of an online learning model should pay attention to the needs of students ' psychology while motivating students to be active during the learning process with the learning model of assurance-relevance-interest-assessment-satisfaction. The method of implementation is to cooperate with the child protection institution of Banten Province in the webinar activities via Zoom and aired live via YouTube. The data collection is a photo-documentation of activities and questionnaires given after the activity to 120 participants. The result is for all aspects (material delivery aspect, aspect of material content, aspect benefit activities) on the poll given more than 50% participants responded: